Girl in translation - Kwok, Jean. (New York : Penguin Books, 2010)
Caught between the pressure to succeed in America, her duty to their family, and her own personal desires, Kimberly Chang, an immigrant girl from Hong Kong, learns to constantly translate not just her language but herself back and forth between the worlds she straddles.
Keywords: Chinese -- New York (State) -- New York -- Fiction; Women immigrants -- Fiction; Chinese American teenagers -- Fiction; Mothers and daughters -- Fiction